Revision of the endemic Malagasy leafhopper tribe Platyjassini (Hemiptera: Cicadellidae: Iassinae) - Dietrich, Christopher H.; MAGALHÃES, Raysa Brito de; Takiya, Daniela M. (European Journal of Taxonomy, 2020)
The leafhopper tribe Platyjassini, endemic to Madagascar, is revised, largely based on specimens obtained in a recent bioinventory project led by the California Academy of Sciences. Platyjassini was previously known based on the type genus, Platyjassus Evans, 1953, and four described species. Betsileonas marmorata (Blanchard, 1840), the largest leafhopper recorded from Madagascar, presently known from a few specimens collected > 100 years ago and recently considered a genus and species incertae sedis within Cicadellidae, is newly placed in Platyjassini. Fourteen new genera and 54 new species are described and illustrated, and three new combinations are proposed. Pachyjassus gen. nov. includes three new species: Pachyjassus alatus sp. nov., Pachyjassus basifurcatus sp. nov. and Pachyjassus ranomafanensis sp. nov. Pallijassus gen. nov. is erected to include two species previously placed in Platyjassus, Pallijassus reticulatus (Evans, 1959) comb. nov. and Pallijassus stenospatulatus (Evans, 1959) comb. nov. Petalojassus gen. nov. includes one new species, Petalojassus ochrescens sp. nov. Phaiojassus gen. nov. includes seven new species: Phaiojassus acutus sp. nov., Phaiojassus bispinosus sp. nov., Phaiojassus constrictus sp. nov., Phaiojassus grandis sp. nov., Phaiojassus spatulatus sp. nov., Phaiojassus undulatus sp. nov. and Phaiojassus unispinosus sp. nov. Pictojassus gen. nov. includes three new species: Pictojassus kirindiensis sp. nov., Pictojassus productus sp. nov. and Pictojassus tulearensis sp. nov. Platyjassella gen. nov. includes six new species: Platyjassella ancora sp. nov., Platyjassella andohahelensis sp. nov., Platyjassella attenuata sp. nov., Platyjassella cormorana sp. nov., Platyjassella emarginata sp. nov. and Platyjassella immaculata sp. nov. Platyjassula gen. nov. includes four new species: Platyjassula cyclura sp. nov., Platyjassula heterofurca sp. nov., Platyjassula isofurca sp. nov. and Platyjassula mahajangensis sp. nov. In addition to the type species, Platyjassus viridis Evans, 1953, Platyjassus includes 11 new species: Platyjassus acutus sp. nov., Platyjassus asymmetricus sp. nov., Platyjassus fisheri sp. nov., Platyjassus griswoldi sp. nov., Platyjassus harinhalai sp. nov., Platyjassus irwini sp. nov., Platyjassus pedistylus sp. nov., Platyjassus pennyi sp. nov., Platyjassus pictipennis sp. nov., Platyjassus symmetricus sp. nov. and Platyjassus vestigius sp. nov. Plerujassus gen. nov. includes one new species, Plerujassus brunnescens sp. nov., in addition to Plerujassus appendiculatus (Evans, 1959) comb. nov., previously placed in Platyjassus. Plexijassus gen. nov. includes one new species, Plexijassus caliginosus sp. nov. Pseudocurtara gen. nov. includes three new species: Pseudocurtara minima sp. nov., Pseudocurtara nigripicta sp. nov. and Pseudocurtara quadrata sp. nov. Pseudocyrta gen. nov. includes one new species, Pseudocyrta hyalina sp. nov. Pseudomarganana gen. nov. includes two new species: Pseudomarganana olivacea sp. nov. and Pseudomarganana rosea sp. nov. Pulchrijassus gen. nov. includes eight new species: Pulchrijassus anjozorobensis sp. nov., Pulchrijassus eunsunae sp. nov., Pulchrijassus pallescens sp. nov., Pulchrijassus roseus sp. nov., Pulchrijassus rubrilineatus sp. nov., Pulchrijassus sindhuae sp. nov., Pulchrijassus talatakelyensis sp. nov. and Pulchrijassus toamasinensis sp. nov. Punctijassus gen. nov. includes three new species: Punctijassus circularis sp. nov., Punctijassus compressus sp. nov. and Punctijassus ivohibensis sp. nov. Illustrated keys to genera and species are provided.